1999
DOI: 10.1246/bcsj.72.943
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions of Pure Long-Chain α,ω-Alkanediols from C13 to C24

Abstract: A series of pure α,ω-alkanediols HO-(CH2)n-OH (n = 13—24) was prepared and the effects of chain length and parity on their thermal properties were investigated. Crystal structures of odd α,ω-alkanediols were orthorhombic, while those of even α,ω-alkanediols were monoclinic. α,ω-Alkanediols with n = 13—24 showed solid–solid transitions except for n = 14. The solid–solid transition was found to be reversible. Transition temperatures from the crystal to the high-temperature phase indicated distinctive and regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
7

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 18 publications
1
17
0
7
Order By: Relevance
“…These heteroatom-containing diols had much lower melting points and enthalpy values than the corresponding purely aliphatic diols. [6,9,24] It has been suggested that ether links activate the rotation of neighboring methylene groups, resulting in an increase in flexibility, which could cause a lowering of the melting temperature. [28] Additionally, unlike the corresponding aliphatic diols, the heteroatom-containing diols did not exhibit a solid-solid rotator phase transition upon heating.…”
Section: Monomer Characterization and Thermal Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These heteroatom-containing diols had much lower melting points and enthalpy values than the corresponding purely aliphatic diols. [6,9,24] It has been suggested that ether links activate the rotation of neighboring methylene groups, resulting in an increase in flexibility, which could cause a lowering of the melting temperature. [28] Additionally, unlike the corresponding aliphatic diols, the heteroatom-containing diols did not exhibit a solid-solid rotator phase transition upon heating.…”
Section: Monomer Characterization and Thermal Propertiesmentioning
confidence: 99%
“…* and * represent data from this paper and literature (see refs. [6,9,24] ), respectively. Scheme 2.…”
Section: Thermal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In these structures, the molecules form a layer structure which is similar to that found in smectic A liquid crystals. In addition, phase transitions in ,3-alkanediols with C 13 ±C 24 were studied and a linear relation between the longest unit-cell length and number of C atoms was reported using powder X-ray diffraction (Ogawa & Nakamura, 1999). Fig.…”
Section: Commentmentioning
confidence: 99%
“…При охлаждении из расплава наблюдается обратная картина: образец выделяет тепло (экзотермический процесс), при T min 2 происходит его кристаллизация, а при T min 1 -твердофазный переход [2,4].…”
unclassified